Hypopneas with arousals: an important feature of central nervous system sympathetic activation in posttraumatic stress disorder - Gupta, Madhulika A. (J Clin Sleep Med, 2020)
Gupta MA. Hypopneas with arousals: an important feature of central nervous system sympathetic activation in posttraumatic stress disorder. J Clin Sleep Med. 2020;16(2):335.